Processing technology of high-elasticity durable leather cloth
By introducing specific materials into the surface finishing agent and applying them to the leather surface, the problems of insufficient folding resistance, wear resistance and dry wet rub resistance of existing leather fabrics are solved, and a high elastic and durable leather fabric is achieved, which improves the overall performance of the material.
Patent Information
- Application Number
- CN202510260825.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-25
AI Technical Summary
The existing leather fabrics have shortcomings in terms of fold resistance, wear resistance and dry wet rub resistance, which affects the actual use effect.
The highly elastic and durable leather fabric is formed by introducing cellulose modified polyurethane resin, concave and convex earth-polycarbonate composite material and modified glass fibers into the surface coating agent and applying the surface coating agent to the surface of the leather.
It effectively improves the folding and wear resistance of leather fabrics, and at the same time obtains good wet and dry rub resistance, improving the overall performance of the material.
Smart Images

Figure BDA0005300465980000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of leather, and in particular relates to a processing technology for high-elasticity and durable leather cloth. Background Art
[0002] With the steady growth of the national economy and the improvement of consumers' living standards, leather products have gained the favor of consumers for their special texture, gloss and comfortable feel. However, due to the special characteristics of leather products, such as strong absorption, easy wrinkling and easy wear, the application of finishing agents in the leather industry to beautify the appearance of leather and simply make the leather have good mechanical properties. Finishing has been recognized as one of the most important processes in the leather industry. Finishing agents are generally composed of polymers with good film-forming properties. A layer of treatment agent applied to the surface of leather is a multi-component mixed system formed by film-forming substances, coloring materials, additives and solvents. Through the bonding effect of film-forming substances, other components are evenly coated on the leather surface to form one or more layers of thin films; among them, polyurethane has attracted much attention due to its special film-forming properties, and leather fabrics formed by the composite of leather and polyurethane finishing agents are also increasingly widely used.
[0003] A Chinese patent (publication number CN116512688B) discloses an environmentally friendly leather composite fabric and its preparation method. The foaming layer of the invention is based on water-based polyurethane resin, and polycarbonate, foaming agent, glass fiber and thickener are added. After foaming, it is formed on the lower surface of the leather layer, which significantly improves the air permeability of the leather composite fabric. At the same time, the addition of polycarbonate and glass fiber significantly improves the mechanical properties of the foaming layer, thereby improving the tear strength of the leather composite fabric. However, the leather fabric obtained by the existing process still has problems such as poor folding resistance, poor wear resistance, and low dry and wet rubbing resistance, which seriously affects actual use.
[0004] Therefore, there is an urgent need for a leather fabric processing technology, which can obtain a highly elastic and durable leather fabric by modifying the components of the surface coating agent, effectively improve the folding resistance, increase the wear resistance, and obtain a good dry and wet rubbing resistance grade. Summary of the invention
[0005] The purpose of the present invention is to provide a processing technology for high-elasticity and durable leather cloth, by introducing cellulose-modified polyurethane resin, attapulgite-polycarbonate composite material and modified glass fiber into a surface coating agent, and coating the surface coating agent on the surface of the leather to obtain a high-elasticity and durable leather cloth, thereby effectively improving the folding resistance and increasing the wear resistance, and obtaining a good dry and wet rubbing resistance grade.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a processing technology for high-elasticity and durable leather cloth, comprising the following steps:
[0008] Step S1: by weight, 50 to 60 parts of cellulose modified polyurethane resin, 12 to 16 parts of attapulgite-polycarbonate composite material and 4 to 8 parts of modified glass fiber are mixed and ground, and then 6 to 10 parts of foaming agent and 1.2 to 1.8 parts of thickener are added and mixed evenly to obtain a surface finishing agent;
[0009] Step S2: applying the surface finishing agent on the surface of the leather, and sequentially drying, dyeing, and antifouling to obtain a highly elastic and durable leather fabric;
[0010] The preparation method of the cellulose modified polyurethane resin comprises: in parts by weight, polyethylene glycol and toluene diisocyanate are reacted once, acetone, 2,2-dihydroxymethylpropionic acid and trimethylolpropane are added for secondary reaction, diethylene glycol, acetone and stannous octoate are added for tertiary reaction, and finally cellulose and acetone are added for sealed stirring to obtain a prepolymer; triethylamine is added to the prepolymer for dispersion and emulsification, and deionized water is added for stirring and distillation to obtain the cellulose modified polyurethane resin.
[0011] As a preferred solution, the preparation method of the cellulose modified polyurethane resin comprises: mixing 60 to 70 parts of polyethylene glycol and 40 to 50 parts of toluene diisocyanate by weight for a primary reaction, then adding 16 to 20 parts of acetone, 6 to 10 parts of 2,2-dihydroxymethylpropionic acid and 1 to 3 parts of trimethylolpropane for a secondary reaction, then adding 8 to 10 parts of diethylene glycol, 16 to 20 parts of acetone and 0.02 to 0.04 parts of stannous octoate for a tertiary reaction, and finally adding 20 to 30 parts of cellulose and 50 to 60 parts of acetone for sealed stirring to obtain a prepolymer; adding 4 to 6 parts of triethylamine to the prepolymer for dispersion and emulsification, then adding 400 to 500 parts of deionized water for high-speed stirring, and distilling to obtain a cellulose modified polyurethane resin.
[0012] As a preferred scheme, the conditions of the primary reaction include: the primary reaction temperature is 90-96°C, and the primary reaction time is 100-120 min; the conditions of the secondary reaction include: the secondary reaction temperature is 76-80°C, and the secondary reaction time is 2-4 h; the conditions of the tertiary reaction include: the tertiary reaction temperature is 68-70°C, and the tertiary reaction time is 1-2 h.
[0013] The cellulose in the cellulose-modified polyurethane resin has a rich hydroxyl structure, which can interact with the carbamate groups in the polyurethane molecular chain through hydrogen bonds to form a tight network structure to enhance the cohesion of the material and improve the folding resistance of the material through a flexible network.
[0014] As a preferred solution, the preparation method of the attapulgite-polycarbonate composite material includes: pretreating 10 to 20 parts of attapulgite by weight, then mixing with 400 to 500 parts of polycarbonate, extruding at 250 to 260° C., cooling, and crushing to obtain the attapulgite-polycarbonate composite material.
[0015] As a preferred scheme, the pretreatment conditions include: adding attapulgite to hydrochloric acid, stirring to react, filtering, washing, and drying to obtain acidified attapulgite; adding the acidified attapulgite to xylene for ultrasonic dispersion, then adding (3-mercaptopropyl)trimethoxysilane, stirring to reflux for reaction, centrifuging, washing, and drying to obtain thiolated attapulgite; dispersing the thiolated attapulgite in toluene, adding caprolactam and styrene, stirring to react, centrifuging, washing, and drying to obtain pretreated attapulgite.
[0016] As a preferred solution, the pretreatment conditions include: adding 10 to 20 parts by weight of attapulgite to 500 to 600 parts by weight of a 1.2 to 1.6 molar mass fraction. l / L hydrochloric acid solution, stirring at 70-80°C for 6-8h, filtering, washing with water until neutral, and drying to obtain acidified attapulgite; adding 10-20 parts of the acidified attapulgite to 1500-1600 parts of xylene, ultrasonicating for 40-60min, then adding 10-16 parts of (3-mercaptopropyl)trimethoxysilane, stirring and refluxing for 14-16h under a nitrogen atmosphere, centrifuging, washing with anhydrous ethanol, and vacuum drying to obtain thiolated attapulgite; dispersing 10-20 parts of the thiolated attapulgite in 400-500 parts of toluene, adding 30-36 parts of caprolactam and 400-500 parts of styrene under a nitrogen atmosphere, stirring at 94-96°C for 16-18h, centrifuging, washing with tetrahydrofuran, and vacuum drying to obtain pretreated attapulgite.
[0017] The attapulgite in the attapulgite-polycarbonate composite material has high hardness and good mechanical properties, and can form a reinforcing phase in the polycarbonate matrix of the composite material. At the same time, the attapulgite surface has a certain lubricity, which can reduce the generation of wear particles during friction, thereby improving the wear resistance of the material.
[0018] As a preferred solution, the preparation method of the modified glass fiber includes: adding 20 to 30 parts of glass fiber by weight to 300 to 400 parts of Tris-hydrochloric acid buffer for ultrasonic dispersion, and then adding 6 to 8 parts of dopamine hydrochloride for coating treatment to obtain modified glass fiber.
[0019] As a preferred solution, the coating treatment conditions include: shaking the coating in a shaker for 24 to 30 hours, filtering, washing with water, and vacuum drying at 90 to 94° C. for 6 to 8 hours.
[0020] After the modified glass fiber is coated with dopamine, the roughness and chemical activity of the glass fiber surface increase. At the same time, the dopamine-coated glass fiber can form a uniform and stable protective layer on the surface of the leather cloth, effectively resisting the friction generated during dry and wet rubbing, thereby improving the level of dry and wet rubbing resistance.
[0021] As a preferred solution, the foaming agent is selected from any one of monofluorodichloroethane, azodicarbonamide, and azobisisobutyronitrile, or a combination of at least two thereof.
[0022] As a preferred solution, the thickener is sodium alginate and carboxymethyl cellulose.
[0023] As a preferred solution, the mass ratio of sodium alginate to carboxymethyl cellulose in the thickener is (1-2):1.
[0024] In order to achieve the above object, the present invention provides the following technical solutions:
[0025] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0026] 1. The cellulose in the cellulose-modified polyurethane resin of the present invention contains a large amount of hydroxyl groups. The dopamine of the modified glass fiber can undergo a Michael addition reaction with the cellulose to form a covalent bond, thereby constructing an interconnected network. When used in conjunction with the attapulgite-polycarbonate composite material, the crack propagation during folding is reduced, while providing high hardness and wear resistance, thereby obtaining a good dry and wet rubbing resistance grade.
[0027] 2. The cellulose in the cellulose-modified polyurethane resin has a rich hydroxyl structure, which can interact with the carbamate groups in the polyurethane molecular chain through hydrogen bonds to form a tight network structure to enhance the cohesion of the material and improve the folding resistance of the material through a flexible network.
[0028] 3. The attapulgite in the attapulgite-polycarbonate composite material has high hardness and good mechanical properties, and can form a reinforcing phase in the polycarbonate matrix of the composite material. At the same time, the surface of the attapulgite has a certain lubricity, which can reduce the generation of wear particles during the friction process, thereby improving the wear resistance of the material.
[0029] 4. After the modified glass fiber is coated with dopamine, the roughness and chemical activity of the glass fiber surface increase. At the same time, the dopamine-coated glass fiber can form a uniform and stable protective layer on the surface of the leather cloth, effectively resisting the friction generated during dry and wet rubbing, thereby improving the level of dry and wet rubbing resistance. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The sources of some components in the embodiments and comparative examples are as follows:
[0032] Polyurethane resin, model AH-1702, purchased from Anhui Anda Huatai New Materials Co., Ltd.;
[0033] Polycarbonate, CAS No. 25037-45-0, purchased from Henan Tianfu Chemical Co., Ltd.;
[0034] 1-Fluoro-1,1-dichloroethane, product number D305163, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0035] Azodicarbonamide, CAS No. 123-77-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0036] Azobisisobutyronitrile, CAS No. 78-67-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0037] Glass fiber, product number S30527, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0038] Sodium alginate, CAS No. 9005-38-3, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0039] Carboxymethyl cellulose, product number C501052, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0040] Polyethylene glycol, product number P103719, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0041] Toluene diisocyanate, CAS No. 26471-62-5, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0042] Acetone, CAS No. 67-64-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0043] 2,2-Dihydroxymethylpropionic acid, CAS No. 4767-03-7, purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0044] Trimethylolpropane, CAS No. 77-99-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0045] Diethylene glycol, CAS No. 111-46-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0046] Triethylamine, CAS No. 121-44-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0047] Stannous octoate, CAS No. 301-10-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0048] Attapulgite, model PalyGel 200, purchased from Anhui Mingmei Mineral Chemical Co., Ltd.;
[0049] Tris-HCl buffer, catalog number T301504, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0050] Dopamine hydrochloride, CAS No. 62-31-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0051] Example 1
[0052] This embodiment provides a processing technology for high-elasticity and durable leather fabric, comprising the following steps:
[0053] Step S1: by weight, 60 parts of cellulose-modified polyurethane resin, 16 parts of attapulgite-polycarbonate composite material and 8 parts of modified glass fiber are mixed and ground, and then 10 parts of a foaming agent, fluorodichloroethane and 1.8 parts of a thickener (1.2 parts of sodium alginate and 0.6 parts of carboxymethyl cellulose) are added and mixed evenly to obtain a surface finishing agent;
[0054] Step S2: applying the surface finishing agent on the surface of the leather, and sequentially drying, dyeing, and antifouling to obtain a highly elastic and durable leather fabric;
[0055] Preparation of the cellulose modified polyurethane resin: by weight, 70 parts of polyethylene glycol and 50 parts of toluene diisocyanate are mixed for a primary reaction (temperature of 96° C., stirring speed of 60 rpm, time of 100 min), then 20 parts of acetone, 10 parts of 2,2-dihydroxymethylpropionic acid and 3 parts of trimethylolpropane are added for a secondary reaction (temperature of 80° C., stirring speed of 60 rpm, time of 2 h), then 10 parts of diethylene glycol, 20 parts of acetone and 0.04 parts of stannous octoate are added for a tertiary reaction (temperature of 70° C., stirring speed of 60 rpm, time of 1 h), finally 30 parts of cellulose and 60 parts of acetone are added for sealed stirring (speed of 60 rpm, time of 20 min) to obtain a prepolymer; 6 parts of triethylamine are added to the prepolymer for dispersion and emulsification, then 500 parts of deionized water are added for high-speed stirring (speed of 800 rpm, time of 6 min), and distilled to obtain a cellulose modified polyurethane resin.
[0056] Preparation of the attapulgite-polycarbonate composite material: by weight, 20 parts of attapulgite are added to 600 parts of a 1.6 molar mass fraction. l / L hydrochloric acid solution, stirred at 80°C for 6h, filtered, washed with water until neutral, and dried to obtain acidified attapulgite; 20 parts of the acidified attapulgite were added to 1600 parts of xylene and ultrasonicated for 60min, then 16 parts of (3-mercaptopropyl)trimethoxysilane were added, stirred and refluxed for 16h under a nitrogen atmosphere, centrifuged, washed with anhydrous ethanol, and vacuum dried to obtain thiolated attapulgite; 20 parts of the thiolated attapulgite were dispersed in 500 parts of toluene, 36 parts of caprolactam and 500 parts of styrene were added under a nitrogen atmosphere, stirred at 96°C for 16h, centrifuged, washed with tetrahydrofuran, and vacuum dried to obtain pretreated attapulgite; 20 parts of the pretreated attapulgite were mixed with 500 parts of polycarbonate, extruded at 260°C, cooled, and crushed to obtain an attapulgite-polycarbonate composite material.
[0057] Preparation of the modified glass fiber: by weight, 30 parts of glass fiber are added to 400 parts of Tris-hydrochloric acid buffer for ultrasonic dispersion, and then 8 parts of dopamine hydrochloride are added for coating treatment, and the coating is shaken in a shaker for 30 hours, filtered, washed with water, and vacuum dried at 94°C for 6 hours to obtain the modified glass fiber.
[0058] Example 2
[0059] This embodiment provides a processing technology for high-elasticity and durable leather fabric, comprising the following steps:
[0060] Step S1: by weight, 50 parts of cellulose modified polyurethane resin, 12 parts of attapulgite-polycarbonate composite material and 4 parts of modified glass fiber are mixed and ground, and then 6 parts of azodicarbonamide, a foaming agent, and 1.2 parts of a thickener (0.6 parts of sodium alginate and 0.6 parts of carboxymethyl cellulose) are added and mixed evenly to obtain a surface finishing agent;
[0061] Step S2: applying the surface finishing agent on the surface of the leather, and sequentially drying, dyeing, and antifouling to obtain a highly elastic and durable leather fabric;
[0062] Preparation of the cellulose modified polyurethane resin: by weight, 60 parts of polyethylene glycol and 40 parts of toluene diisocyanate are mixed for a primary reaction (temperature of 90° C., time of 120 min), then 16 parts of acetone, 6 parts of 2,2-dihydroxymethylpropionic acid and 1 part of trimethylolpropane are added for a secondary reaction (temperature of 76° C., time of 4 h), then 8 parts of diethylene glycol, 16 parts of acetone and 0.02 parts of stannous octoate are added for a tertiary reaction (temperature of 68° C., time of 2 h), finally 20 parts of cellulose and 50 parts of acetone are added for sealed stirring (speed of 70 rpm, time of 15 min) to obtain a prepolymer; 4 parts of triethylamine are added to the prepolymer for dispersion and emulsification, then 400 parts of deionized water are added for high-speed stirring (speed of 1000 rpm, time of 4 min), and distilled to obtain a cellulose modified polyurethane resin.
[0063] Preparation of the attapulgite-polycarbonate composite material: by weight, 10 parts of attapulgite are added to 500 parts of a 1.2 mol l / L hydrochloric acid solution, stirred at 70°C for 8h, filtered, washed with water until neutral, and dried to obtain acidified attapulgite; 10 parts of the acidified attapulgite were added to 1500 parts of xylene and ultrasonicated for 40min, then 10 parts of (3-mercaptopropyl)trimethoxysilane were added, stirred and refluxed for 14h under a nitrogen atmosphere, centrifuged, washed with anhydrous ethanol, and vacuum dried to obtain thiolated attapulgite; 10 parts of the thiolated attapulgite were dispersed in 400 parts of toluene, 30 parts of caprolactam and 400 parts of styrene were added under a nitrogen atmosphere, stirred at 94°C for 18h, centrifuged, washed with tetrahydrofuran, and vacuum dried to obtain pretreated attapulgite; 10 parts of the pretreated attapulgite were mixed with 400 parts of polycarbonate, extruded at 250°C, cooled, and crushed to obtain an attapulgite-polycarbonate composite material.
[0064] Preparation of the modified glass fiber: by weight, 20 parts of glass fiber are added to 300 parts of Tris-hydrochloric acid buffer for ultrasonic dispersion, and then 6 parts of dopamine hydrochloride are added for coating treatment, and the coating is shaken in a shaker for 24 hours, filtered, washed with water, and vacuum dried at 90°C for 8 hours to obtain the modified glass fiber.
[0065] Example 3
[0066] This embodiment provides a processing technology for high-elasticity and durable leather fabric, comprising the following steps:
[0067] Step S1: In parts by weight, 55 parts of cellulose-modified polyurethane resin, 14 parts of attapulgite-polycarbonate composite material and 6 parts of modified glass fiber are mixed and ground, and then 8 parts of azobisisobutyronitrile as a foaming agent and 1.4 parts of a thickener (0.8 parts of sodium alginate and 0.6 parts of carboxymethyl cellulose) are added and mixed evenly to obtain a surface finishing agent;
[0068] Step S2: applying the surface finishing agent on the surface of the leather, and sequentially drying, dyeing, and antifouling to obtain a highly elastic and durable leather fabric;
[0069] Preparation of the cellulose modified polyurethane resin: by weight, 65 parts of polyethylene glycol and 45 parts of toluene diisocyanate are mixed for a primary reaction (temperature of 93° C., time of 110 min), then 18 parts of acetone, 8 parts of 2,2-dihydroxymethylpropionic acid and 2 parts of trimethylolpropane are added for a secondary reaction (temperature of 78° C., time of 3 h), then 9 parts of diethylene glycol, 18 parts of acetone and 0.03 parts of stannous octoate are added for a tertiary reaction (temperature of 69° C., time of 2 h), finally 25 parts of cellulose and 55 parts of acetone are added for sealed stirring (speed of 65 rpm, time of 15 min) to obtain a prepolymer; 5 parts of triethylamine are added to the prepolymer for dispersion and emulsification, then 450 parts of deionized water are added for high-speed stirring (speed of 900 rpm, time of 5 min), and distilled to obtain a cellulose modified polyurethane resin.
[0070] Preparation of the attapulgite-polycarbonate composite material: by weight, 15 parts of attapulgite are added to 550 parts of a 1.4 mol l / L hydrochloric acid solution, stirred at 75°C for 7h, filtered, washed with water until neutral, and dried to obtain acidified attapulgite; 15 parts of the acidified attapulgite were added to 1550 parts of xylene, ultrasonicated for 50min, and then 12 parts of (3-mercaptopropyl)trimethoxysilane were added, stirred and refluxed for 15h under a nitrogen atmosphere, centrifuged, washed with anhydrous ethanol, and vacuum dried to obtain thiolated attapulgite; 15 parts of the thiolated attapulgite were dispersed in 450 parts of toluene, 32 parts of caprolactam and 450 parts of styrene were added under a nitrogen atmosphere, stirred at 95°C for 17h, centrifuged, washed with tetrahydrofuran, and vacuum dried to obtain pretreated attapulgite; 15 parts of the pretreated attapulgite and 450 parts of polycarbonate were melt-blended, extruded at 255°C, cooled, and crushed to obtain an attapulgite-polycarbonate composite material.
[0071] Preparation of the modified glass fiber: by weight, 25 parts of glass fiber are added to 350 parts of Tris-hydrochloric acid buffer and ultrasonically dispersed evenly, then 7 parts of dopamine hydrochloride are added for coating treatment, and the coating is shaken in a shaker for 28 hours, filtered, washed with water, and vacuum dried at 92°C for 7 hours to obtain the modified glass fiber.
[0072] Comparative Example 1
[0073] The difference between this comparative example and Example 1 is that a commercially available polyurethane resin (model AH-1702) is used to replace the cellulose-modified polyurethane resin.
[0074] Comparative Example 2
[0075] The difference between this comparative example and Example 1 is that commercially available polycarbonate (CAS No. 25037-45-0) is used to replace the attapulgite-polycarbonate composite material.
[0076] Comparative Example 3
[0077] The difference between this comparative example and Example 1 is that commercially available glass fiber (article number S30527) is used to replace the cellulose modified glass fiber.
[0078] Comparative Example 4
[0079] The difference between this comparative example and Example 1 is that the amount of sodium alginate in the thickener is changed to 1.5 parts, and the amount of carboxymethyl cellulose is changed to 0.3 parts.
[0080] Comparative Example 5
[0081] The difference between this comparative example and Example 1 is that the amount of sodium alginate in the thickener is changed to 0.6 parts, and the amount of carboxymethyl cellulose is changed to 1.2 parts.
[0082] Performance Testing
[0083] The leather fabrics of the above embodiments and comparative examples were subjected to the following tests:
[0084] (1) Folding resistance test: The test is carried out in accordance with the requirements of GB / T 3819-1997 Determination of crease recovery of textile fabrics - Recovery angle method. The test results are expressed as the average number of cracks.
[0085] (2) Abrasion resistance test: The abrasion resistance of leather fabric was tested using a Byes-101-4Z Martindale abrasion tester. A leather fabric sample with a diameter of 38 mm was prepared. A 2.5 kg pressure plate was placed in the center of the grinding table. The load shaft was passed through the small hole on the plate and then the circular groove was adjusted so that the load shaft was inserted into the circular groove of the test fixture. The instrument was started using a standard rubber grinding wheel and stopped after the specified number of frictions was reached. The abrasion resistance of the sample was evaluated in an environment with sufficient but not direct light.
[0086] (3) Wet and dry abrasion resistance test: The wet and dry abrasion resistance tester CJ9E I was used to measure the wet and dry abrasion resistance of the leather surface. The test conditions were as follows: the load was 80 g / cm 3 The friction speed is 43 times / min and the friction stroke is 6mm.
[0087] Table 1 Performance test results
[0088]
[0089] It can be seen from the above performance test results that the leather cloth prepared by the processing technology of Examples 1-3 has the best comprehensive effect, with a small average number of cracks, a wear grade of 0, a dry rub resistance grade of 5, and a wet rub resistance grade of 5; this is mainly because it introduces cellulose-modified polyurethane resin, attapulgite-polycarbonate composite material and modified glass fiber into the surface coating agent, and coats the surface coating agent on the surface of the leather to obtain a highly elastic and durable leather cloth, which effectively improves the folding resistance, increases the wear resistance, and obtains a good dry and wet rub resistance grade.
[0090] Compared with Example 1, Comparative Example 1 uses commercially available polyurethane resin (model AH-1702) to replace cellulose modified polyurethane resin, and the folding resistance becomes worse, the wear resistance decreases, and the dry and wet rubbing resistance decreases; Compared with Example 1, Comparative Example 2 uses commercially available polycarbonate (CAS No. 25037-45-0) to replace attapulgite-polycarbonate composite material, and the folding resistance becomes worse, the wear resistance decreases, and the dry and wet rubbing resistance decreases; Compared with Example 1, Comparative Example 3 uses commercially available glass fiber (item No. S30527) to replace cellulose modified glass fiber, and the folding resistance becomes worse. deteriorated, the wear resistance decreased, and the resistance to wet and dry rubbing decreased; compared with Example 1, the amount of sodium alginate in the thickener of Comparative Example 4 was changed to 1.5 parts, and the amount of carboxymethyl cellulose was changed to 0.3 parts. Due to the excessive amount of sodium alginate, the compounding effect was not good, the folding resistance deteriorated, the wear resistance decreased, and the resistance to wet and dry rubbing decreased; compared with Example 1, the amount of sodium alginate in the thickener of Comparative Example 5 was changed to 0.6 parts, and the amount of carboxymethyl cellulose was changed to 1.2 parts. Due to the small amount of sodium alginate, the compounding effect was not good, the folding resistance deteriorated, the wear resistance decreased, and the resistance to wet and dry rubbing decreased.
Claims
1. A processing technology for high elastic and durable leather fabric, characterized in that: The following steps are involved: Step S1: by weight, 50 to 60 parts of cellulose modified polyurethane resin, 12 to 16 parts of attapulgite-polycarbonate composite material and 4 to 8 parts of modified glass fiber are mixed and ground, and then 6 to 10 parts of foaming agent and 1.2 to 1.8 parts of thickener are added and mixed evenly to obtain a surface finishing agent; Step S2: applying the surface finishing agent on the surface of the leather, and sequentially drying, dyeing, and antifouling to obtain a highly elastic and durable leather fabric; The preparation method of the cellulose modified polyurethane resin comprises: reacting polyethylene glycol and toluene diisocyanate once, adding acetone, 2,2-dihydroxymethylpropionic acid and trimethylolpropane for secondary reaction, adding diethylene glycol, acetone and stannous octoate for tertiary reaction, and finally adding cellulose and acetone to seal and stir to obtain a prepolymer; adding triethylamine to the prepolymer for dispersion and emulsification, adding deionized water for stirring, and distilling to obtain the cellulose modified polyurethane resin.
2. The processing technology of a high elastic and durable leather cloth according to claim 1, characterized in that: The temperature of one reaction is 90-96°C and the time is 100-120 minutes.
3. The processing technology of a highly elastic and durable leather fabric according to claim 1, characterized in that: The temperature of the secondary reaction is 76-80°C and the time is 2-4 hours; the temperature of the tertiary reaction is 68-70°C and the time is 1-2 hours.
4. The processing technology of a high elastic and durable leather fabric according to claim 1, characterized in that: The preparation method of the attapulgite-polycarbonate composite material comprises: pre-treating 10 to 20 parts of attapulgite by weight, then mixing with 400 to 500 parts of polycarbonate, extruding at 250 to 260° C., cooling, and crushing to obtain the attapulgite-polycarbonate composite material.
5. The processing technology of a high elastic and durable leather fabric according to claim 4 is characterized in that: The pretreatment conditions include: adding attapulgite to hydrochloric acid, stirring for reaction, filtering, washing, and drying to obtain acidified attapulgite; adding the acidified attapulgite to xylene for ultrasonic dispersion, then adding (3-mercaptopropyl)trimethoxysilane, stirring for reflux reaction, centrifuging, washing, and drying to obtain thiolated attapulgite; dispersing the thiolated attapulgite in toluene, adding caprolactam and styrene, stirring for reaction, centrifuging, washing, and drying to obtain pretreated attapulgite.
6. The processing technology of a high elastic and durable leather fabric according to claim 1, characterized in that: The preparation method of the modified glass fiber comprises: adding 20 to 30 parts of glass fiber to 300 to 400 parts of Tris-hydrochloric acid buffer by weight for uniform ultrasonic dispersion, and then adding 6 to 8 parts of dopamine hydrochloride for coating treatment to obtain the modified glass fiber.
7. The processing technology of a high elastic and durable leather fabric according to claim 6, characterized in that: The coating treatment conditions include: shaking the coating in a shaker for 24 to 30 hours, filtering, washing with water, and vacuum drying at 90 to 94° C. for 6 to 8 hours.
8. The processing technology of a high elastic and durable leather fabric according to claim 1, characterized in that: The foaming agent is selected from any one of monofluorodichloroethane, azodicarbonamide, and azobisisobutyronitrile, or a combination of at least two thereof.
9. The processing technology of a high elastic and durable leather fabric according to claim 1, characterized in that: The thickeners are sodium alginate and carboxymethyl cellulose.
10. The processing technology of a high elastic and durable leather cloth according to claim 9, characterized in that: The mass ratio of sodium alginate to carboxymethyl cellulose in the thickener is (1-2):1.
Citation Information
Patent Citations
Environmentally friendly leather composite fabric and preparation method thereof
CN116512688B
Polycarbonate compound and preparation method thereof
CN114276661A
Modified glass fiber, method for modifying glass fiber by using dopamine and reinforced polyamide 6 composite material
CN116332531A
Environment-friendly leather composite fabric and preparation method thereof
CN116512688A
Leather finishing agent and preparation method thereof
CN116606578A